Penny Postcard of the Pierpont Inn, Ventura, CA - United States Post Office
Penny postcards were introduced in the United States in 1873, by Post Master John Creswell. This postcard is of the Pierpont Inn, located on Sanjon Road in Ventura, CA. The hotel opened for business in September 1910.